Did Hospital Admissions Caused by Respiratory Infections and Asthma Decrease During the COVID-19 Pandemic? - Zeynep Reyhan ONAY; Deniz MAVI; Yetkin AYHAN; Sinem CAN OKSAY; Gulay BILGIN; Saniye GIRIT (Medeniyet Medical Journal)
Objective: Despite maximum isolation measures taken during the coronavirus disease-2019 (COVID-19) pandemic, the workload of health institutions has increased. Consequently, changes in the number of admissions in clinics and emergency departments by disease groups have been observed. We aimed to quantitatively investigate the changes in the frequency of respiratory infections and asthma in the pediatric population during the COVID-19 pandemic. Methods: We analyzed electronic medical record data of patients who were admitted to the emergency department (ED), outpatient and inpatient clinics, and pediatric intensive care unit (PICU) because of influenza, upper and lower respiratory tract infections (URTI, LRTI), acute bronchiolitis, and asthma during the two-year period (one year pre- COVID period and first year of the pandemic). Results: There were 96,648 admissions in the pre-COVID period and 15,848 during the pandemic. We observed a decline in ED admissions (-73%), outpatient clinic visits (-70%), hospitalizations (-41.5%), and PICU admissions (-42%). While the admission rates of patients with influenza [from 4.26% to 0.37% (p=0.0001)] and URTI [from 81.54% to 75.62% (p=0.0001)] decreased, the ratio of the number of admissions to the total number of admissions due to LRTI [from 8.22% to 10.01% (p=0.0001)], acute bronchiolitis [from 2.76% to 3.07% (p=0.027)], and asthma [from 5.96% to 14% (p=0.0001)] increased. Conclusions: The decrease in viruses that cause acute bronchiolitis and asthma attacks lead to a reduction in admissions to ED of this patient group. The fact that parents preferred not to admit their child in ED during this period may have paved the way for the development of more severe LRTIs.